National Nursing Home Survey, 1997 ([Verlag nicht ermittelbar], 2000)
The National Nursing Home Survey (NNHS) is a survey of nursing homes and related care facilities in the United States. Between July and December 1997, information regarding facility and financial characteristics was gathered from 1,406 facilities, along with current resident information for 8,138 residents. For Part 1, Facility Questionnaire Data, personal interviews with facility administrators provided information on topics such as certification, availability of beds, and kinds of services provided, including dental, hospice, and nutrition. Part 2, Current Resident Questionnaire Data, provides information on age, race, marital status, level of care, and use of aids such as walkers, hearing aids, and crutches. Part 3, Discharged Resident Questionnaire Data, includes date of admission, reason for discharge, admission diagnosis, discharge diagnosis, assistive devices used, help needed with daily activities, services provided (health, mental health, transportation, social, educational), and payment sources.